(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the nursing team’s knowledge before and after an online educational intervention about the care and maintenance of short-term central venous catheters in critically ill adults. Method: A quasi-experimental study of the pre and post type developed with the nursing staff of a University Hospital where a knowledge test form was applied before and after an educational intervention in the form of online training. Results: Twenty-one nurses and 20 nursing technicians participated in the study, totaling 41 participants. A descriptive analysis was conducted, considering the total score, that is, the hits achieved in the questionnaire, with all participants and for the professional categories participating in the research (nurses and nursing technicians) in the pre- and post-intervention moment, where an increase in the mean number of hits was evidenced, as well as a reduction in the variance in the post-intervention moment. A total of 30 participants increased their scores, that is, 73.2% of the sample showed a better performance on the questionnaire. Conclusion: The educational intervention resulted in improved scores on the post-intervention questionnaire. It is believed that the results of this study allow the development of other strategies for the development and evaluation of the nursing team’s knowledge about the theme addressed.